Preoperative Evaluation of Craniopagus Twins: Anatomy, Imaging Techniques, and Surgical Management - Goldman-Yassen, A.E.; Goodrich, J.T.; Miller, T.S.; Farinhas, J.M. (American Journal of Neuroradiology, 2020)
SUMMARY: Craniopagus twins are a rare congenital malformation in which twins are conjoined at the head. Although there is high prenatal and postnatal mortality for craniopagus twins, successful separation has become more common due to advances in neuroimaging, neuroanesthesia, and neurosurgical techniques. Joined brain tissue, shared arteries and veins, and defects in the skull and dura make surgery technically challenging, and neuroimaging plays an important role in preoperative planning. Drawing on our experience from consultation for multiple successful separations of craniopagus twins, we discuss what radiologists need to know about the anatomy, classification, imaging techniques, and surgical management of craniopagus twins.CPTcraniopagus twinsCVScircumferential venous sinusSDVSshared dural venous sinusesTAtotal angularTVtotal vertical